A new species of the mealybug genus Ceroputo Šulc 1898 (Hemiptera: Coccomorpha: Pseudococcidae) from China, and notes on Ceroputo pilosellae Šulc 1898 in China - Zhang, Jiang-Tao; Watson, Gillian W. (Zootaxa, 2023)
A new mealybug species, Ceroputo liquidambaris Zhang & Watson sp. n. (Hemiptera: Coccomorpha: Pseudococcidae), collected on leaves and branches of Liquidambar formosana (Altingiaceae), is described and illustrated from Jiangxi, China. The new species differs from all other known species of Ceroputo in having dorsal multilocular disc pores. Notes on some aspects of Ceroputo pilosellae Šulc collected in China and a key to the adult females of Ceroputo species are provided.